The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.chb.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of media multitasking for youth: A review

Abstract: a b s t r a c tThe increasing prevalence of media multitasking among youth has raised concerns regarding its negative effects on youths' functioning. Although the number of empirical studies on the consequences of media multitasking for youth has grown rapidly, there has been no attempt to integrate theory with the results of these studies. This review integrates available findings on the relationship between media multitasking and three domains of youths' functioning: cognitive control, academic performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
203
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(237 citation statements)
references
References 80 publications
10
203
2
3
Order By: Relevance
“…Initial evidence from cross-sectional and experience sampling research has also linked Facebook use to impaired overall well-being among students (Kross et al, 2013;Satici & Uysal, 2015). Experimental research by Sagioglou and Greitemeyer (2014) further indicates that Facebook use impairs affective well-being (e.g., current mood) because it is perceived as "less meaningful, less useful, and more of a waste of time" than other (online) activities (p. 361).…”
Section: Consequences Of Procrastination With Facebookmentioning
confidence: 89%
“…Initial evidence from cross-sectional and experience sampling research has also linked Facebook use to impaired overall well-being among students (Kross et al, 2013;Satici & Uysal, 2015). Experimental research by Sagioglou and Greitemeyer (2014) further indicates that Facebook use impairs affective well-being (e.g., current mood) because it is perceived as "less meaningful, less useful, and more of a waste of time" than other (online) activities (p. 361).…”
Section: Consequences Of Procrastination With Facebookmentioning
confidence: 89%
“…26 Two systematic reviews have shown that media multitasking is associated with negative effects on cognitive control, academic performance and socioemotional functioning in youth. 27,28 Most existing studies, however, are cross-sectional, and measures are heterogenous across studies with limited attempts to consider individual and contextual differences, making it impossible to establish causality. Youth with lower impulse control may be more susceptible to deleterious effects of media multi tasking.…”
Section: Does Social Media Addiction Exist and Can It Affect Mental Hmentioning
confidence: 99%
“…A large body of research has shown that interruptions during work-or school-related activities lead to lower task performance, higher perceived stress, and mental fatigue (Eyrolle & Cellier, 2000;Jett & George, 2003). In the school context, studies have shown that engaging in media while doing homework or being in class is related to diminished processing of study content and decreased learning (for a review, see Van der Schuur et al, 2015). For example, Armstrong and Greenberg (1990) have shown that background television led to impaired reading comprehension, spatial problem solving, and cognitive flexibility.…”
Section: Engagement In Computer-based Multitaskingmentioning
confidence: 99%
“…needed for finishing a task (Bowman, Levine, Waite, & Gendron, 2010;Eyrolle & Cellier, 2000), and lower academic performance (for reviews, see Carrier, Rosen, Cheever, & Lim, 2015;Jeong & Hwang, 2016;Van der Schuur, Baumgartner, Sumter, & Valkenburg, 2015).…”
mentioning
confidence: 99%